Detection of Two Species of the Genus Parapoxvirus (Bovine Papular Stomatitis Virus and Pseudocowpox Virus) in Ticks Infesting Cattle in Burkina Faso - Achille Ouedraogo; Léa Luciani; Olivier Zannou; Abel Biguezoton; Laura Pezzi; Laurence Thirion; Adrien Belem; Claude Saegerman; Rémi Charrel; Laetitia Lempereur (Microorganisms, 2020)
The molecular identification of arboviruses in West Africa is of particular interest, due to their zoonotic potential in a population living in close contact with livestock, and in a region where the livestock migration across borders raises the risk of diseases infection and dissemination. The aim of the study was the screening of potential circulating arboviruses and the assessment of their zoonotic implications. Therefore, ticks were collected on cattle located in three provinces of eastern Burkina Faso. Tick pools were tested using a panel of genus-specific real-time assays targeting conserved regions of parapoxvirus, orthopoxvirus, flavivirus and phlebovirus. On the 26 farms visited, a total of 663 ticks were collected. Four genera and six tick species were morphologically identified, with Amblyomma variegatum and Hyalomma spp. being the most represented species. No arboviruses were found. However, this study highlights the presence of pseudocowpox virus (8.2%) and bovine papular stomatitis virus (5.8%) among the positive tick pools. BPSV positive ticks were found in herds sharing water and pastures resources and with a history of seasonal transhumance. Therefore, common grazing and the seasonal transhumance are likely to support the transmission of the virus. This could have important health and economic impacts, especially regarding transboundary cattle movements.